Modern membrane coverings and their usage standards in long span structures - Ramzi Alshaikh; Mirna Nassra; Cecile Kannab (Tishreen University, 2019)
ازدادت الحاجة إلى استخدام مواد بناء حديثة تدعم الجمل الإنشائية للمباني وذلك نتيجةً للتطور العلمي والتقني الذي شمل مختلف أساليب الإنشاء من جهة, واستمراراً للسعي الدائم لتحقيق مبدأ الاستدامة في المنشآت المعمارية من جهة أخرى, وذلك بتعزيز كفاءة هذه المباني على ترشيد الطاقة والقدرة على إنتاج طاقات بديلة, إضافة إلى الاستفادة من مواد البناء الحديثة في التقليل من التكاليف وضمان سهولة التنفيذ والصيانة لدورها في التقليل من تلوث الطبيعة واستنزاف مواردها. يتناول البحث رصدا للتغطيات الغشائية الحديثة المستخدمة في المنشآت الفراغية وتطورها, بالتركيز على التغطيات الغشائية التي ظهرت اواخر القرن العشرين وأوائل القرن الواحد والعشرين, بدءاً من التطرق إلى تعريف ماهية الأنسجة الغشائية المستخدمة في تغطية الفراغات الواسعة, وأنواعها, وأسس اختيارها, ومعرفة ميزات هذه المواد، ومن ثم تطبيق ذلك في دراسة تحليلية لبعض المباني ذات التغطيات الغشائية الحديثة بهدف تقييم أداء هذا النوع من التغطية في تحقيق الجودة الوظيفية والجمالية للمبنى . أشار البحث إلى أهمية مواد البناء الحديثة المطورة في التقليل من استهلاك الطاقة والموارد الطبيعية, ودور هذه المواد في رفع  كفاءة الأداء الوظيفي للمنشآت ومساهمتها في تعزيز البنية الجمالية الحديثة لمختلف أنواع المباني, مع التأكيد على ضرورة تطويع هذه التجربة ومعرفة طريقة الاستخدام الأمثل لخدمة المباني والمنشآت المختلفة الأنواع. The need has increased to use modern building materials to support the construction formulations of buildings as a result of progresses that spanned the various construction styles and sustainability efforts of the architectural construction; these efforts aimed at increasing buildingsefficiency, savingand producing alternative power sources, reducing costs and ensuring the ease of implementation and maintenance due to their role in reducing the pollution of nature and resource waste. The purpose of this research is to observe the modern shell encasements of the vacuum construction and their progress between the end of 20th century and the beginning of 21th century, byaddressing the shell fabricsdefinition, their types, selection criteria, materialsspecification; and perform an analytical study of some modern shell encasement buildings to evaluatethis encasement type in terms of functionality and innovation. The research has concluded the importance of the modified, modern building materials in saving power and natural resources, increasing the efficiency of the functional performance, contributing to the modern, innovative structure of the various buildingtypes, and emphasizing the importance of adapting this experience and reaching the optimum utilization waysin various buildings and construction structurestypes.